Prevalence and Abundance of Ixodid Ticks in Domestic Mammals in Villages at the Forest Fringes of the Western Ghats, India - Hari Kishan Raju; Ayyanar Elango; Ranganathan Krishnamoorthi; Manju Rahi (Animals, 2025)
Kyasanur Forest Disease (KFD), first reported in 1957 in the Shimoga district of Karnataka, India, has spread significantly over the past two decades, reaching both northern and southern states, with reports of monkey deaths. Haemaphysalis spp. ticks are the primary vectors, transmitting the disease to monkeys, humans, and other mammals. This study aimed to assess the prevalence, mean abundance, and mean intensity of Ixodidae ticks, including the KFD vector, in domestic animals across selected localities of the Western Ghats. A total of 2877 domestic animals were surveyed, revealing an overall tick prevalence of 44.91% (CI: 43.10–46.73), with sheep showing the highest prevalence at 47.92% (CI: 40.96–54.95). The most abundant tick species was Rhipicephalus (Boophilus) microplus, with a mean of 2.53 ± 0.66 ticks per host, which also represented the most proportionally dominant species, accounting for 39.63% of the total ticks collected. The highest mean intensity was recorded for Haemaphysalis intermedia (7.35 ± 2.03 ticks per infested animal). Regionally, Rh. (Bo.) microplus was found in 96.15% of buffaloes examined in Tamil Nadu, Haemaphysalis bispinosa in 85.19% of cattle in Maharashtra, and in 98.46% of goats in Goa. Ha. intermedia was common in 99.11% of sheep examined in Karnataka, while Ha. bispinosa was observed in 90.82% of goats in Kerala. The proportional representation of the KFD vector Haemaphysalis spinigera was 0.97%, with a mean intensity of 2.34 ± 0.04 ticks per infested animal and an overall mean abundance of 0.06 ± 0.01 ticks per host. Adult Ha. spinigera were recorded from cattle, buffaloes, sheep, goats, and dogs; however, no nymphs were detected. This study also reports the first documented occurrence of Ixodes ceylonensis in domestic animals. These findings suggest a notable presence of tick infestations in the region and emphasize the importance of continued surveillance and targeted control measures to better understand and manage potential KFD transmission risks in the Western Ghats.